STUDY OF HUMOR IN THE USE OF JAVANESE LANGUAGE ON THE INSTAGRAM ACCOUNT "D_KADOOR" - Daristin, Pipit ertika; Rohmatul Fitriyah Dewi (E-Link Journal, 2024)
In the digital era, the rapid development of technology and freedom of expression encourage individuals to create new sensations such as 'creating humor' . The content presented in the media is not much different from the topics discussed in public . Media can develop linguistically in the manifestation of humor . This research aims to determine the characteristics of humor, namely the principles of humor and satire through the use of Javanese language used by Kadir Bachmid in monologue videos uploaded to his Instagram account , "D_kadoor" . This research is a qualitative research . The data for this research is the uploaded video "D_kadoor" which contains a conversational monologue created by Kadir Bachmid. The data source was taken from the Instagram account "D_kadoor" . The research results obtained are as follows. First, the author finds humor characteristics which include fun with words, mixing styles, language in context and clever connections. Second, the element of satire as part of humor is realized through humor in the Javanese language, namely Kadoor following the social context of today's life. Therefore, this research shows that the existence of humor is a reflection of human social life. Apart from that, Javanese language still exists and is packaged creatively. So, Kadoor's post can have a positive impact on social media users, especially Instagram.